Back Cover: Metal‐Directed Self‐Assembly of a Polyoxometalate‐Based Molecular Triangle: Using Powerful Analytical Tools to Probe the Chemical Structure of Complex Supramolecular Assemblies (Chem. Eur. J. 52/2015). Issue 52 (21st December 2015) - Izzet, Guillaume; Macdonell, Andrew; Rinfray, Corentin; Piot, Madeleine; Renaudineau, Séverine; Derat, Etienne; Abécassis, Benjamin; Afonso, Carlos; Proust, Anna
Abstract : A combination of 1 H NMR, 2D diffusion NMR spectroscopy, electrospray ionization travelling wave ion‐mobility mass spectrometry, small‐angle X‐ray scattering, and molecular modelling allowed the unambiguous characterization of an original covalent polyoxometalate‐based molecular triangle. More details of this fascinating chemistry can be found in the Full Paper by G. Izzet and co‐workers onpage 19010 ff.